Patents and Sustainable Medical Treatment in Developing Countries: Lessons from COVID-19 Vaccines - Demir, Ezgi; Bican, Peter (Sustainability, 2023)
COVID-19 has had devastating effects worldwide, and vaccines have become the most efficient solution to address the current pandemic situation thus far. After COVID-19 vaccines had been developed, discussions of the various countries' equality of access gained traction, with patents and pricing forming a significant part of this discourse. Therefore, this study investigates the impact of patents and prices on the accessibility of COVID-19 vaccines in the developing world, using semi-structured interviews with subject-matter experts in this area of focus. Our analysis of these interviews highlights the fact that patents and prices are not the major barriers to accessibility for medical treatments, both generally and specifically in terms of COVID-19; rather, these barriers relate to the lack of local production capacity, technology transfer, infrastructure, local regulations, and supply-chain competencies. These results suggest that rather than focusing on patents and prices, governments should invest more time in improving technology transfer and using compulsory licenses as a negotiation tool. Moreover, the results show that the pricing strategies applied by companies could have different impacts on access, as could accessibility programs such as COVAX.
CRIS-Team WoS Importer:2023-03-24
Keywords: COVID-19 pandemic; patent; intellectual property; vaccines; developing countries; sustainable medication; sustainability; healthcare; Inklusion